2019
DOI: 10.1080/15384047.2019.1599659
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of MicroRNA-21 promotes tumorigenesis of prostate cancer cells by targeting KLF5

Abstract: Prostate cancer (PCa) is the second frequently newly diagnosed cancer in men. Androgen deprivation therapy has been widely used to inhibit PCa growth but eventually fails in many patients. Androgen receptor and its downstream molecules like microRNAs could be promising therapeutic targets. We aimed to investigate the involvement of miR-21 in PCa tumorigenesis. We found that miR-21 was an unfavorable factor and correlated positively with tumor grade in PCa patients from TCGA database. MiR-21 was more highly exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 54 publications
3
27
0
Order By: Relevance
“…[20][21][22] Aberrant miRNA expression has been frequently identified in PCa and demonstrated to be closely associated with prostate carcinogenesis, including PCa progression. [23][24][25] In addition, miRNAs are regarded as perfect candidates for identifying tumor diagnosis and prognosis biomarkers. 26,27 Therefore, an in-depth exploration of PCa-related miRNAs may offer novel insights into the molecular pathways underlying PCa progression and facilitate the identification of novel targets for anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Aberrant miRNA expression has been frequently identified in PCa and demonstrated to be closely associated with prostate carcinogenesis, including PCa progression. [23][24][25] In addition, miRNAs are regarded as perfect candidates for identifying tumor diagnosis and prognosis biomarkers. 26,27 Therefore, an in-depth exploration of PCa-related miRNAs may offer novel insights into the molecular pathways underlying PCa progression and facilitate the identification of novel targets for anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-125b is involved in regulating NF-κB, p53, PI3K/AKT/mTORC1, ERBB2, WNT, and other signaling pathways, thereby controlling cell proliferation, differentiation, metabolism, apoptosis, drug resistance, and tumor immunity. MiR-21 is another oncogenic miR overexpressed in PCa that inhibits various tumor suppressor genes such as PTEN enhancing mTORC1 activation [ 334 , 335 , 336 , 337 , 338 , 339 , 340 , 341 , 342 , 343 , 344 ].…”
Section: Milk-induced Overactivation Of Mtorc1 and Diseases Of CIVmentioning
confidence: 99%
“…Previous studies indicated that these miRNAs could modulate cancer microenvironment or tumor transformation. miR-21 overexpression promoted tumorigenesis in prostate [ 28 ] and cervical [ 29 ] cancers. Also, miR-21 upregulation increased chemoresistance in lung adenocarcinoma [ 30 ], invasiveness and angiogenesis in renal carcinoma [ 31 ] and lymphoma [ 32 ].…”
Section: Main Bodymentioning
confidence: 99%